Analisi Tes Butir Soal Uraian Pada Pembelajaran PAI Dengan Menggunakan Taksonomi Bloom Di Sd N Gedongtengen, Yogyakarta - Nurul Muti’ah; Maemonah Maemonah (Raudhah - Proud To Be Professional, 2022)
Abstract The aim of this research is to analyze the mid-semester exam questions for Islamic Religious Education at SD N Gedongtengen, with an emphasis on Anderson's Taxonomy and Bloom's Krathwohl revision. The research results show that these questions are cognitively appropriate and consistent with applicable programs and indicators. In grade 4, questions cover cognitive levels from C2 (Comprehension) to C4 (Analysis). In class 5, the questions cover levels from C2 to C5 (Assessment). Meanwhile in class 6, the question that reaches the highest cognitive level is C6 (Creativity). In this research, researchers used data collection techniques which included techniques, interviews, and observation and documentation. The object of the research is the teacher of Islamic religious education subjects, while the object of the research is the analysis of mid-term exam description questions for grades 4, 5 and 6 at SD N Gedongtengen. The research results illustrate that the preparation of questions takes into account students' cognitive level and follows the oldest guidelines in the syllabus and learning indicators, so that it has the potential to support efforts to increase students' understanding and reflection abilities in learning. field of Islamic religious education. Keywords: Analysis of question items, Islamic Religious Education, Bloom's Taxonomy. AbstrakTujuan penelitian ini untuk menganalisis soal-soal ujian tengah semester Pendidikan Agama Islam di SD N Gedongtengen, dengan penekanan pada Taksonomi Anderson dan revisi Krathwohl karya Bloom. Hasil penelitian menunjukkan bahwa pertanyaan-pertanyaan tersebut sesuai secara kognitif dan konsisten dengan program dan indikator yang berlaku. Di kelas 4, soal mencakup tingkat kognitif dari C2 (Pemahaman) hingga C4 (Analisis). Di kelas 5, soal mencakup level dari C2 hingga C5 (Penilaian). Sedangkan di kelas 6, soal yang mencapai tingkat kognitif tertinggi adalah C6 (Kreativitas). Pada penelitian ini peneliti menggunakan teknik pengumpulan data yang meliputi teknik, wawancara, dan observasi dan dokumentasi. Objek penelitiannya adalah guru mata pelajaran pendidikan agama Islam, sedangkan objek penelitiannya adalah analisis soal uraian ujian tengah semester kelas 4, 5 dan 6 SD N Gedongtengen. Hasil penelitian menggambarkan bahwa penyusunan soal memperhatikan tingkat kognitif siswa dan mengikuti pedoman yang tertuang dalam silabus dan indikator pembelajaran, sehingga berpotensi mendukung upaya peningkatan pemahaman dan kemampuan refleksi siswa dalam pembelajaran. bidang pendidikan agama islam.